KARAKTERISTIK SIFAT MEKANIS DAN STRUKTUR MIKRO PROSES AUSTEMPER PADA BAJA KARBON S 45 C DAN S 60 C - Lim Richie Stifler; Sobron Yamin Lubis; Erwin Siahaan (Program Studi Teknik Mesin Universitas Tarumanagara, 2017)
Abstract: Steel is an iron-carbon alloys containing concentrations of other alloys having a different composition and treatment materials, steel properties can be changed by heat treatment. The heat treatment process serves to increase the strength of a steel material. The nature of the material can be turned into a more robust and resilient heat treatment process, if done properly and correctly. Austempering process is just one example of the heat treatment process at steel that aims to improve the mechanical properties of the steel S 45 C and S 60 C. austempering process performed on the steel S 45 C and S 60 C aims to increase the hardness and toughness of the steel. Austempering process is done by austenisasi advance with temperature 8500C and held for 60 minutes, after which the process is carried out with 3 election austempering temperature of 3500C, 4500C, 5500C and held for 30 minutes. The method used to test the results of austempering is tensile testing using ASTM A370- 12a, Vickers hardness test and microstructure observation using a digital microscope. In the test results tensile steel S 45 C and S 60 C values obtained an increase in ductility and toughness of 17.1 % on steel S 45 C and 17 % on steel S 60 C. This value is obtained from the calculation of ultimate tensile strength test specimens that have not been in austempering process with a specimen that has been in the process of austempering at 3500C , and the results of testing hardness of the steel S 45 C and S 60 C obtained hardness value of 44% increase in steel S 45 C and 46 % on steel S 60 C. value this is obtained from the calculation of the average value of the test specimen is not in the process of austempering with a specimen that has been in the process of austempering at 3500C .